2023
DOI: 10.3114/sim.2023.105.01
|View full text |Cite
|
Sign up to set email alerts
|

A genome-informed higher rank classification of the biotechnologically important fungal subphylum Saccharomycotina

Abstract: The subphylum Saccharomycotina is a lineage in the fungal phylum Ascomycota that exhibits levels of genomic diversity similar to those of plants and animals. The Saccharomycotina consist of more than 1 200 known species currently divided into 16 families, one order, and one class. Species in this subphylum are ecologically and metabolically diverse and include important opportunistic human pathogens, as well as species important in biotechnological applications. Many traits of biotechnological interest are fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 160 publications
1
28
0
Order By: Relevance
“…Since the ITS2 sequence of strain P34-5 and the ITS1 sequence of strain OTU674 are not available for comparison, they are not included in the phylogenetic trees. | 543 from those resolved based on the whole-genome sequences (Groenewald et al, 2023;Shen et al, 2018). The present study shows that the closest relatives of the Yueomyces species are…”
Section: Phylogenetic Analysismentioning
confidence: 64%
See 2 more Smart Citations
“…Since the ITS2 sequence of strain P34-5 and the ITS1 sequence of strain OTU674 are not available for comparison, they are not included in the phylogenetic trees. | 543 from those resolved based on the whole-genome sequences (Groenewald et al, 2023;Shen et al, 2018). The present study shows that the closest relatives of the Yueomyces species are…”
Section: Phylogenetic Analysismentioning
confidence: 64%
“…Vanderwaltozyma and Torulaspora species with strong bootstrap supports (Figure 1). However, Shen et al (2018) and Groenewald et al (2023) showed that Y. sinensis is most closely related to Tetrapisispora blattae, followed by Vanderwaltozyma polyspora and four other Tetrapisispora species. We show here that T. blattae CBS 6284 is located in a separate branch, which is not closely related to the Yueomyces species nor to the other five Tetrapisispora species compared in this study (Figure 1).…”
Section: Phylogenetic Analysismentioning
confidence: 95%
See 1 more Smart Citation
“…These distances were then clustered using standard average hierarchical clustering to visualize the raw growth rates on a heatmap built using heatmap3 in R. The phylogeny of 1,154 yeasts and fungal outgroups built from 2,408 orthologous groups of genes. Branches are colored according to their taxonomic assignment to an order of Saccharomycotina (46). The innermost rings are colored by the top-level type of isolation environment in which each specific strain was isolated.…”
Section: Extrinsic Factor Analysesmentioning
confidence: 99%
“…The genome-based phylogeny obtained from sequences representing 332 yeast species demonstrated that the genus Danielozyma clustered with the genus Hyphopichia in the CUG-Ser1 clade [5]. The genus is presently classified in the family Debaryomycetaceae within the order Serinales, class Pichiomycetes, the subphylum Saccharomycotina [6].…”
Section: Introductionmentioning
confidence: 99%